Stability and thermo-physical properties of green bio-glycol based TiO2-SiO2 nanofluids - S. N. M., Zainon; W. H., Azmi (Elsevier, 2021)
The investigation on thermal properties of nanoparticles dispersed in the mixture of water and green Bio-glycol are limited in the literature and only available for single nanofluids. The purpose of this study is to investigate the stability and thermo-physical properties of green Bio-glycol based TiO2-SiO2 nanofluids. In the present study, the hybrid nanofluids were prepared at various volume concentrations of 0.5 to 3.0% by dispersing TiO2 and SiO2 nanoparticles (20:80) in water and Bio-glycol (40:60) mixture base fluids. The stability of green Bio-glycol based TiO2-SiO2 nanofluids showed physically to be in good range of stability for suspension nanoparticles with zeta potential of